Gambaran Kesenangan Belajar IPA dan Ketertarikan Berkarir di Bidang IPA Siswa Sekolah Menengah Pertama - Sari, Nirmala; ika, Erika (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2020)
This article aims to present the results of research on students' attitudes towards science subjects in terms of two indicators, namely interest in learning science and career interest in science among junior high school students. This associative quantitative research uses a survey on a research sample of 128 students. The data analysis technique used is descriptive statistics. The results of the data analysis showed that the students' attitudes on the indicators of interest in learning science were dominant in the good category, while the attitudes of the students on the indicators of career interest in science were dominant in the moderate category.